Customers' Satisfaction and Loyalty: Examining the roles of Safety and Religiosity - Rahmadhiani, Ighfirlana Alief; Nurdin, Ridwan; Amri, Khoirul; Halim, Hendra; Sari, Nurma; Irwandi, Irwandi (Universitas Syiah Kuala, 2025)
This study aims to analyze the effect of security and religiosity on user loyalty of KOALA ojek transportation services on USK students with satisfaction as a mediating variable. The sample in this study amounted to 100 respondents using the Slovin formula and the sampling method in this study used probability sampling with a stratified random sampling approach. The data analysis technique used SPSS version 25 and the analysis method used in this research is path analysis. The results showed that security and religiosity had a significant positive effect on user satisfaction and loyalty. In addition, satisfaction was shown to mediate the relationship between security and religiosity on user loyalty. These findings provide important insights for service providers to improve security aspects and align with people's religious values, in order to create a better user experience and increase loyalty.